Pendampingan Pembuatan dan Penerapan Alat Peraga Matematika bagi Guru SD Gugus II Kecamatan Amanuban Barat - Prida N. L. Taneo; Farida Daniel; Yusak I. Bien (Prodi PGSD FIP UNM, 2018)
The results of the situation analysis related to mathematics learning in 2 partner schools in the cluster II of the West Amanuban sub-district, namely SD Inpres Oenali and SD Inpres Oefatu showed that the implementation of abstract mathematics learning and sticking to textbooks was very minimal, the existence of mathematics teaching aids was minimal, the teacher's ability in the manufacture of mathematics teaching aids is still lacking, KKG meetings and district-level trainings are more directed at learning administration activities and have not touched on the essence of mathematics learning such as teaching aids design. The solution to this problem is the transfer of science and technology to teachers in the form of mentoring in the making and application of mathematics teaching aids. The method of implementing this activity is in the form of training and mentoring carried out by adopting action research steps through four stages, namely planning, implementing, observing and evaluating and reflecting. The results of this activity are increasing the ability and skills of teachers in the making and application of mathematics teaching aids that allow students to do mathematical activities by using teaching aids in classroom learning.